Insightful The Precious Reflection Of Volunteer Nurses Caring For Covid-19 Patients - Ira Kusumawaty; Yunike Yunike; Gunardi Pome (Poltekkes Kemenkes Surakarta, 2021)
Background: The shock of the Covid-19 transmission forced the implementation of learning methods by volunteer nurses during the academic period of learning. Nurse volunteers face the complexities of dealing with Covid-19 as the backbone of saving the unavoidable Covid-19 victims. However, the exploration of the valuable experience of volunteer nurses is still minimal, even though the information provided has implications for efforts to improve the health care system during a pandemic. This study reports on the experience of volunteer nurses in hospitals in treating Covid-19 patients. Methods: This qualitative research uses a phenomenological approach. Purposive sampling technique was used to determine the sample, the exploratory process involved seven volunteer nurses and two head nurses through in-depth interviews and observations to obtain an in-depth narrative about the volunteer nurse experience. This research was conducted in two hospitals located in South Sumatera Province. The process of data analysis was carried out using the Colaizzi’s method. The formulation of the theme begins with the writing of the transcript, the formulation of coding, categories, sub-themes until finally the formulation of the theme. The ethical clearance has been submitted prior to the conduct of the study and has been declared to have passed the ethical review. Results: Based on the results of Colaizzi's analysis, three themes have been formulated, namely the driving factors for volunteering, preparation as a volunteer nurse and events caring for Covid-19 patients. Conclusion: This research implies that it is necessary to modify the volunteer nurses in interacting and communicating with patients and contacting the families of volunteer nurses to increase the retention of volunteer nurses.